Model Tata Kelola Air Belhamagu: Tinjauan Pustaka Keberlanjutan dan Reformasi Administrasi Pelayanan Air - Rafi Kholikin; Dumanita Tamba; Adi Irfan Marjuqi (Universitas Cahaya Prima, 2026)
This study conducts a systematic literature review of the Belhamagu communal water governance model in Belu Regency, East Nusa Tenggara, Indonesia. Following the PRISMA guidelines, an initial identification of 495 documents from Scopus, Web of Science, Google Scholar, and DOAJ (2014–2024) was screened based on inclusion criteria: peer-reviewed articles, theses/dissertations, or official government reports; focus on institutional, governance, or sustainability aspects of communal water management; geographic context of Indonesia or similar socio-ecological regions; and availability in Indonesian or English. After a layered screening process, 25 publications were selected for in-depth thematic analysis. The findings reveal that Belhamagu operates on communal institutional principles aligned with Ostrom’s design theory, featuring non-hierarchical kinship-based structures, graduated sanction systems, and seasonally adjusted water allocation rules. The model not only ensures sustainable water access but also generates public value through social cohesion, distributive justice, and ecosystem preservation. The study contributes theoretically to collaborative governance (by demonstrating subsidiarity and power asymmetry), public value management (water as a social right versus commodity), adaptive governance (non-hierarchical feedback loops), and administrative reform (proposing a hybrid governance model that integrates local wisdom into formal public policy). This research addresses critical knowledge gaps by building theoretical bridges between local practices and global discourse, offering a blueprint for inclusive, responsive, and context-sensitive public sector transformation in Indonesia and beyond.